2019
DOI: 10.4149/neo_2018_180825n647
|View full text |Cite
|
Sign up to set email alerts
|

The value of detecting pepsinogen and gastrin-17 levels in serum for pre-cancerous lesion screening in gastric cancer

Abstract: The aim of the study was to estimate the value of detecting pepsinogen (PG) I, PGII and gastrin-17 (G-17) levels in serum for chronic atrophic gastritis (CAG) screening and to determine the clinical applicability of combined measurement of serum G-17, pepsinogens (PGI, PGII) and PGI/PGII ratio (PGR) as a screening test for CAG. The PGI, PGII and G-17 levels were detected by ELISA in 68 patients with CAG and 86 healthy volunteers who underwent gastroscopy for gastroduodenal diseases at Taizhou Municipal Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
2
20
1
Order By: Relevance
“…Moreover, the speci city was signi cantly lower than that of the Scoring System from JPHC (p < 0.001) and Li's Scoring System (p < 0.001). Consistent with previous research, the ABC method for gastric cancer screening did not work well in the Chinese populations, with lower sensitivity and speci city than those in nonChinese studies [23][24]. This may be related to the fact that the ABC method was developed in Japanese populations, and the optimal PG and G-17 cut-off values may not be applicable to screening for gastric cancer in China.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the speci city was signi cantly lower than that of the Scoring System from JPHC (p < 0.001) and Li's Scoring System (p < 0.001). Consistent with previous research, the ABC method for gastric cancer screening did not work well in the Chinese populations, with lower sensitivity and speci city than those in nonChinese studies [23][24]. This may be related to the fact that the ABC method was developed in Japanese populations, and the optimal PG and G-17 cut-off values may not be applicable to screening for gastric cancer in China.…”
Section: Discussionsupporting
confidence: 68%
“…Among the family of gastrin, G-17 particularly plays a critical role in the regulation of gastric acid secretion 43 . Some other researches similarly found high level of serum gastrin was associated with precancerous lesions and gastric cancer in Asians [44][45][46][47] . The results of the present study demonstrated that the prevalence of atrophic gastritis tended to increase from benign to malignant lesion.…”
Section: Discussionmentioning
confidence: 87%
“…However, recent studies found that gastrin was closely associated with GC and precancerous lesions [13,[25][26][27]. Moreover, Yu et al found that serum gastrin level could be used for screening pre-cancerous lesion in gastric cancer [28]. These suggested the possible role of gastrin in the diagnosis of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum gastrin is caused by lots of conditions, including GC [11], suggesting gastrin can be used as a potential marker for the diagnosis of GC. Recently, some researchers evaluated the value of detecting gastrin-17 levels in serum for precancerous lesion screening in GC, but reports on assessing the effect of gastrin in the diagnosis of GC were very few [12][13]. Therefore, the effect of gastrin in the diagnosis of GC should be clari ed further.…”
Section: Introductionmentioning
confidence: 99%